Bonifacio ang unang pangulo - Williams, Enzo. (Pasig City Tuko Film productions, Inc., 2014)
Bonifacio: ang unang pangulo is a historical action epic that brings to light the true to life story of Philippine National hero, Andres Bonifacio, with his virtues and umanity, unfolding through the eyes of a high school student.
Tuko Fil productions, Buchi Boy Films and RCP Production present and Enzo Williams film "Bonifacio: ang unang pangulo" Robin Padilla, Vina Morales, Daniel Padilla, Jasmine Curtis Smith, Joem Bascon, Cholo Barretto, Junjun Quintana, Richard Quan, Isabel Oli, RJ Padilla, Ping Medina, Romel Padilla, Isko Moreno, E.A. Rocha with special participation of Jericho Rosales, director of photography Carlo Mendoza, production design Roy Lachica, costume design Joel Bilbao, sound design Mike Idioma, music Von de Guzman, editors Benjamin Tolentino, screenplay by Keiko Aquino, Enzo Williams, Carlo Obispo, producers E.A. Rocha, Rina Navarro, executive producers Fernando Ortigas, Rommel Padilla, Atty. Danilo Patron, directed by Enzo Williams.
Keywords: Philippines -- History -- Cavite Mutiny, 1872.; Philippines -- History -- 1872-1897.